O060 Staged hybrid single lumen reconstruction (TIGER) in management of chronic symptomatic complex type B aortic dissection. (22nd July 2022) - Sultan, S; Acharya, Y; Hynes, N
Abstract: Introduction: We aim to report an innovative technique - Staged Hybrid Single Lumen Reconstruction (TIGER) in the management of chronic symptomatic complex type B aortic Dissection (CS -TBAD). TIGER technique was adopted as a tool for total aortic remodelling with true lumen expansion, false lumen regression and complete thrombosis with stabilization of overall aortic diameter. Methods: Aortic dissection cases (n = 5) were managed by the TIGER technique, which included creating a single lumen from the supra celiac, infra-diaphragmatic aorta to both common iliac arteries with open surgical patching of the visceral arteries; followed by TEVAR three months later (mean follow-up 16 months). All had aneurysmal dilation, while 60% had acute pan aortic dissection and 40% CS-TBAD. Results: Sixty percentages of the patients required a left subclavian artery chimney graft, while 20% required bilateral subclavian to carotid artery transposition. No spinal drainage was needed and all patients had intra-operative trans-oesophageal ECHO for wire guidance. There was no aortic rupture or retrograde type A dissection, and renal, visceral, cardiac, pulmonary, or spinal complications. All, but one patient, went off their antihypertensive medication. 100% of the patients maintained normal eGFR postoperatively with accelerated aortic modulation. Conclusion: Our experience showed that TIGER is effective at the semi acute stage to initiate remodelling and prevent malperfusion, facilitating straightforward TEVAR at stage two, which was made easier by avoiding visceral branch stenting. Moreover, the stented aortic segment's length was decreased, avoiding critical shattering, branch dislodgment, and visceral compromise, including spinal ischaemia and negative cardiovascular consequences. Take-home message: Staged Hybrid Single Lumen Reconstruction (TIGER) is an effective technique in the management of chronic symptomatic complex type B aortic dissection at the semi acute stage to initiate remodelling and prevent malperfusion, facilitating a straightforward thoracic endovascular aortic repair (TEVAR) made easier by avoiding visceral branch stenting.